Porous yolk-shell Fe/Fe3O4 nanoparticles with controlled exposure of highly active Fe(0) for cancer therapy. (January 2021) - Liang, Huan; Guo, Jingru; Shi, Yiyue; Zhao, Guizhen; Sun, Shouheng; Sun, Xiaolian
Abstract: The iron-based Fenton-type reaction has drawn tremendous attention in cancer therapy. Compared with oxidized iron, Fe(0) possesses high catalytic activity but unstable for biomedical application. Here, we report a new strategy to stabilize Fe(0) via a porous yolk shell nanostructure of Fe/Fe3 O4 (PYSNPs) in normal physiological condition, and to control the release of Fe(0) in tumor microenvironment for enhanced cancer therapy. These PYSNPs display superior tumor inhibition with the IC50 down to 20 μg/mL (over 1 mg/mL for iron oxide nanoparticles as control) for HepG2 cell. A single intravenous injection of as low as 1 mg/kg dosage is effective to suppress tumor growth in vivo . Moreover, the disintegration of PYSNPs in the acidic tumor microenvironment could cause significant change in MRI signal for contrast-enhanced diagnosis. Of note, the resulting Fe3 O4 fragments are renal clearable with minimized side effect. In all, this work represented a nanoplatform to stabilize and selectively deliver Fe(0) for highly effective cancer therapy. Graphical abstract: Image 1